2013
DOI: 10.1111/cdev.12206
|View full text |Cite
|
Sign up to set email alerts
|

Crawling and Walking Infants See the World Differently

Abstract: How does visual experience change over development? To investigate changes in visual input over the developmental transition from crawling to walking, thirty 13-month-olds crawled or walked down a straight path wearing a head-mounted eye-tracker that recorded gaze direction and head-centered field of view. Thirteen additional infants wore a motion-tracker that recorded head orientation. Compared with walkers, crawlers’ field of view contained less walls and more floor. Walkers directed gaze straight ahead at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
230
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 247 publications
(237 citation statements)
references
References 66 publications
5
230
1
1
Order By: Relevance
“…Common sense intuition, endorsed by Piaget (1954), Gibson (1988), and Campos (2000), is that independent mobility allows infants to identify distal goal objects and employ crawling as a means to attain those goals. However, common sense intuition is not supported by recent observations (Adolph et al, 2012; Karasik et al, 2011; Kretch et al, in press) or the current studies. Natural infant locomotion—crawling or walking—does not consist of long paths terminating in arrival at a pre-specified goal.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Common sense intuition, endorsed by Piaget (1954), Gibson (1988), and Campos (2000), is that independent mobility allows infants to identify distal goal objects and employ crawling as a means to attain those goals. However, common sense intuition is not supported by recent observations (Adolph et al, 2012; Karasik et al, 2011; Kretch et al, in press) or the current studies. Natural infant locomotion—crawling or walking—does not consist of long paths terminating in arrival at a pre-specified goal.…”
Section: Discussioncontrasting
confidence: 99%
“…Sitting is an important facilitator of development because it opens up new opportunities for exploration and learning. The upright posture affords new views of the world and the people who inhabit it (Cashon, Ha, Allen, & Barna, 2013; Frank, Simmons, Yurovsky, & Pusiol, 2013; Kretch, Franchak, & Adolph, in press). The hands are freed from a supporting role, providing new opportunities for reaching, exploring objects, and learning about object properties (Gibson, 1988; Harbourne et al, 2013; Lobo & Galloway, 2008; Soska & Adolph, 2014).…”
mentioning
confidence: 99%
“…In other words, the transition from crawling to walking, as it is marked by the onsets of standing and walking, is a crucial period for the infant. Walking allows for a different perception of the world than crawling does (Kretch et al, 2014). The mentioned factors might also be related to executive functions without implying a direct link between motor development and executive functions development.…”
Section: Discussion Study IIImentioning
confidence: 99%
“…The emergence of new motor skills, such as reaching or walking, is important, as these skills offer new possibilities for action and perception. Reaching for an object presents opportunities to explore and manipulate different shapes and materials, for example, and walking allows infants to explore space and socially interact with others in a qualitatively different way (Adolph & Tamis-LeMonda, 2014;Kretch, Franchak, & Adolph, 2014;Thelen, 1995). According to the dynamical systems approach, these transitions in development (e.g.…”
Section: Motor Developmentmentioning
confidence: 99%
“…Human eye gaze has been correlated with visual focus of attention [8,9,11], and tends to agree with head direction. Kretch et al instrumented infants with eye trackers and found that most infant eye gaze fixations occur within the middle of the child's field of view [15]. Stiefelhagen et al performed a related study with four adults interacting at a meeting table, and found that eye gaze agreed 87% of the time with the direction of the subject's head [29].…”
Section: Related Workmentioning
confidence: 99%